A Need Analysis in Developing Project-Based Writing Assessment Module to Stimulate Students’ Critical Thinking and Creativity - Bharati , Dwi Anggani Linggar; Lestari , Tutik (KnE Social Sciences, 2019)
Thiscasestudyaimedatevaluatinganexistingwritingassessmentwhichcanstimulate the students’ critical thinking and creativity of SMA students. Moreover, this study investigated the type of assessment needed by SMA students to stimulate their critical thinking and creativity. The writing assessment evaluation was carried out through a need analysis. The subjects of this study were the English teachers and the tenth grade students of SMAN 12 Semarang in the academic year of 2017/2018. Questionnaire, interview, classroom observation, and teacher’s document observation were used as the instrument in collecting the data. This study utilized the qualitative descriptive design which tends to ﬁnd the data by observing the context directly and then a data interpretation was conducted. The major ﬁndings showed that the teacher got difﬁculty in developing a higher-order thinking assessment which can stimulate students’ critical thinking and creativity. In addition, the English teachers had already known and applied the project-based writing assessment, but he never did any development of project-based writing assessment which can stimulate the students’ critical thinking and creativity. The assessment should be based on the 2013 curriculum characteristics and it should refer to the top tree level of Bloom’s cognitive taxonomy namely analyzing, evaluating, and creating. Keywords: Project Base Writing, Senior High School, Assesment